2007
DOI: 10.1002/14651858.cd001943.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Loxapine for schizophrenia

Abstract: Analysis 2.10. Comparison 2 LOXAPINE versus TYPICAL ANTIPSYCHOTICS, Outcome 10 Mental state: 1d. General-average change score (BPRS, high score=worse

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
0
35
0
2
Order By: Relevance
“…4 Acute agitation associated with psychiatric diseases often results in severe distress to patients and their caregivers and is a major contributor to the ongoing stigmatization of mental illness. 5 Oral loxapine, introduced more than 35 years ago in the United States, Canada, and Europe, has a well-established efficacy and safety profile in the treatment ofschizophrenia, 6,7 and an intramuscular formulation was previously approved for the treatment of agitation. [8][9][10][11] Its antipsychotic effects are similar to those of other antipsychotics such as haloperidol and are likely attributable to its actionat dopamine D2 receptors.…”
mentioning
confidence: 99%
“…4 Acute agitation associated with psychiatric diseases often results in severe distress to patients and their caregivers and is a major contributor to the ongoing stigmatization of mental illness. 5 Oral loxapine, introduced more than 35 years ago in the United States, Canada, and Europe, has a well-established efficacy and safety profile in the treatment ofschizophrenia, 6,7 and an intramuscular formulation was previously approved for the treatment of agitation. [8][9][10][11] Its antipsychotic effects are similar to those of other antipsychotics such as haloperidol and are likely attributable to its actionat dopamine D2 receptors.…”
mentioning
confidence: 99%
“…Loxapine is a well-known, midpotency, typical antipsychotic. Loxapine has had a number of head-to-head trials for schizophrenia and a Cochrane study found that loxapine is an option for schizophrenic patients who require rapid tranquilization [24]. Alexza Pharmaceuticals has completed Phase I-III studies on a combination medication-delivery system; Staccato loxapine.…”
Section: Resultsmentioning
confidence: 99%
“…The review included 41 studies, comparing loxapine to haloperidol, thiothixene, risperidone, clozapine and quetiapine. Another finding was that loxapine exhibited a similar degree of adverse events compared with the typical and atypical agents [24].…”
Section: Review Nordstrommentioning
confidence: 92%
See 1 more Smart Citation
“…O ral loxapine, introduced more than 35 years ago in the United States, Canada, and Europe, has a wellestablished efficacy and safety profile in the treatment of schizophrenia, (1,2) and an intramuscular formulation was previously approved for the treatment of agitation. (3)(4)(5)(6) Its antipsychotic effects are similar to those of other antipsychotics such as haloperidol, and are likely attributable to its action at dopamine D2 receptors.…”
Section: Introductionmentioning
confidence: 99%